2019
DOI: 10.1016/j.addbeh.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Not getting high with a little help from your friends: Social versus drug network correlates of marijuana use among YMSM

Abstract: Substantial evidence has documented the importance of social connections in shaping health and drug use behaviors among adolescents and young adults. The current study extends previous research into the associations between network characteristics and drug use behavior among young men who have sex with men (YMSM) by 1) examining multiple network characteristics, 2) simultaneously assessing multiple network types (i.e., social and drug use), and 3) examining change in network characteristics and drug use behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…On the other hand, disruptive social relationships can also trigger a relapse of drug use [ 62 , 63 , 64 ]. Therefore, precautions should be taken when initiating social support, for example, by helping the client and CSOs develop healthy activities and mutual interests for a positive and healthy social network [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, disruptive social relationships can also trigger a relapse of drug use [ 62 , 63 , 64 ]. Therefore, precautions should be taken when initiating social support, for example, by helping the client and CSOs develop healthy activities and mutual interests for a positive and healthy social network [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peer influence and accessibility: Shaping marijuana use among university students Peer influence is a potent force in shaping the attitudes and behaviours of university students towards marijuana use. Numerous studies have consistently underlined the significant role of peers in the initiation and continuation of substance use, particularly marijuana (Hahlbeck & Vito, 2022;Janulis et. al, 2019;Vogel et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Drug users were more likely to have higher education. The impact of education levels on drug use mostly laid in extensive social networking and availability for drugs [7]. One study also found that it was di cult for those with university education levels to attain an appropriate support network for avoiding recreational drug use, thus leading to drug use [36].…”
Section: Additive Interaction Between Recreational Drug Use and Uai Omentioning
confidence: 99%
“…Compared with the older MSM, YMSM were in their sexually active period and might have more sexual activities. Moreover, owing to freshness, thrill-seeking and peer in uence [6][7][8][9], they were more likely to use recreational drugs when engaging in sexual behaviors. Data from World Health Organization (WHO) also indicated that YMSM were more vulnerable to HIV and had a greater HIV risk than heterosexual young people or older MSM [10], which implied they were a special population to be concerned.…”
Section: Introductionmentioning
confidence: 99%